Effects of Reticulated Hyaluronic Acid Alone or Associated With Whole-Body Vibration in Dogs With Osteoarthritis Due to Hip Dysplasia - Martins, David J.C. [UNESP]; Rahal, Sheila C. [UNESP]; Silva Júnior, José I.C. [UNESP]; Michelon, Fernanda [UNESP]; Tomacheuski, Rúbia M. [UNESP]; Correia, Luiz E.C.S. [UNESP]; Woods, Lia S. [UNESP]; Mamprim, Maria J. [UNESP]; Lourenço, Maria L.G. [UNESP]; Santos, Ivan F.C. [UNESP] (My University, 2022)
This study aimed to evaluate the effects of reticulated hyaluronic acid (HA) alone or associated with whole-body vibration (WBV) in dogs with osteoarthritis due to hip dysplasia. Fourteen dogs were randomized assigned into 2 groups of 7 animals: Group 1 (G1) — single intra-articular injection of hyaluronic acid; Group 2 (G2) — single intra-articular injection of hyaluronic acid associated with WBV sessions. The affected hip joint received 0.70 mL of reticulated HA guided by ultrasound. Dogs were submitted to a single session of WBV (30 and 50 Hz, for 15 min) every 48 hours for 12 weeks. Dogs were evaluated for morphometric measurements; orthopedic, radiographic and lameness scores of the hip joints; kinetic analysis; and ultrassonographic measurement of the following muscles: middle gluteal, vastus lateralis and biceps femoris. The morphometric measurements, lameness scores, and muscle measurements were conducted at 10 minutes before treatments (TP0), and at days 30 (TP30), 60 (TP60) and 90 (TP90) after treatments. The orthopedic and radiographic scores and kinetic analysis were performed at TP0 and TP90. The scores of lameness showed a statistical decrease in G1 and G2 between time-points. Significant decreases (P =.01) were observed in orthopedic scores in both groups between time-points. The Peak Vertical Force between TP0 and TP90 was significantly higher in G2 (P =.01). Vertical Impulse was null in G1 and positive in G2. Dogs treated with single intra-articular injection of hyaluronic acid alone and associated with WBV had beneficial effects in dogs with osteoarthritis due to hip dysplasia, however the association of viscosupplementation with hyaluronic acid and WBV had an earlier improvement clinical outcome and allowed better kinetic results.
Keywords: kinetic gait; lameness; mechanic vibration; vibrating platform; viscosupplementation